Jonathan Dickinson and the Formative Years of American Presbyterianism - LeBeau, Bryan F. (Book collections on Project MUSE., 1997)
During the eighteenth century Presbyterians of the Middle Colonies were separated by divergent allegiances, mostly associated with groups migrating from New England with an English Puritan background and from northern Ireland with a Scotch-lrish tradition. Those differences led first to a fiery ordeal of ecclesiastical controversy and then to a spiritual awakening and a blending of diversity into a new order, American Presbyterianism. Several men stand out not only for having been tested by this ordeal but also for having made real contributions to the new order that arose from the controversy.